Lymphoblastic lymphoma in children and adolescents: review of current challenges and future opportunities. (27th February 2019) - Burkhardt, Birgit; Hermiston, Michelle L.
Summary: Lymphoblastic lymphoma (LBL) is the second most common type of Non‐Hodgkin Lymphoma (NHL) in childhood and adolescence, accounting for 25–35% of all cases. The majority, 70–80%, is of T‐lymphoblastic origin while 20–25% arise from B lymphoblasts. With current therapy, the event‐free and overall survivals for paediatric LBL patients now exceeds 80%. Therapy, especially in T‐LBL with large mediastinal tumours, is challenging, with both significant morbidity and late sequela. An additional challenge is the dismal prognosis of patients with refractory or relapsed disease. This review article will focus on the growing knowledge of the pathogenesis and biology of LBL, recent advances and challenges in the therapy of LBL, and ongoing and future efforts and opportunities in optimizing therapy and developing novel targeted treatment approaches.